Distribution Of Some Heavy Metals in Soils of Abu-Ghraib Land, Baghdad, Iraq - Ali , Noor A.; Abdullah, Enaam J. (Iraqi Journal of Science, 2024)
Heavy metals and metalloids can accumulate in the soil, cause severe risks to human health and the ecosystem, and threaten the sustainable use and management of soil resources. This study investigated the Distribution and levels of heavy metals in soils of different lands in Abu-Ghraib (AGP), Baghdad, Iraq. Twenty-seven samples from cultivated soil and two uncultivated soil samples were collected during February 2023 from the surface layer (0–30 cm depth) and analyzed for major oxides and heavy metals. Different parameters were utilized to investigate the naturality of studied soils, including grain size analysis, pH, total dissolved solids (TDS), electrical conductivity (EC), and trace elements (TEs) concentration. Analysis of grain size indicated that all soil samples were silty clay. The mean pH of the collected soils was 7.9, indicating its alkaline nature. Also, the mean of EC and the TDS of the studied soils was 801.55 μS/cm and 0.80155dS/m, respectively, referring to their non-salinity. Mineralogical analysis by XRD indicated the presence of non-clay minerals, such as calcite, quartz, feldspar, and dolomite, and clay minerals, such as illite, kaolinite, and palygorskite. Levels of Al2O3, CaO, Fe2O3, K2O, MgO, P2O5, and SiO2 were interchangeably found high in both types of soils, with CaO (19.84ppm), MgO (7.18ppm), and TiO2 (0.78ppm) being slightly higher in the uncultivated soils. TE concentrations followed a descending order of Mn> Cr> Ni> V> Zn> Cu> Pb> Co> Mo> As> Th> Cd> U> Se in the cultivated soils and Mn> Cr> Ni> V> Zn> Co> Cu> Pb> Mo> Th> As> Cd> U> Se in the uncultivated soils. The results also showed that the concentrations of Cr (262.36> 200ppm), Mo (10.87> 10ppm), Ni (190.24> 150ppm), and V (157.68> 150ppm) acceded the maximum allowable concentrations. Such elevated concentrations of TEs in Abu-Ghraib soils are concerning and may lead to abnormal plant growth, reduced biodiversity, and increased risk of human health problems.